Cult Affiliation of Мidğæw Sanctuary in Village of Lisri (North Ossetia) - A. V. Darchiev (Научный диалог)
The article is devoted to the study of the sanctuary of Midkhau (Мidğæw), located in the mountain village of Lisri in North Ossetia. Due to its unusual “ziggurat” form, the sanctuary is considered unique not only for Ossetia, but also for the entire North Caucasus. Its comprehensive study is an urgent scientific task, since it sheds light on the early stages of the formation of the material and spiritual culture of the Ossetians. The problematic of the versions linking this sanctuary with the cults of the deities Uacilla and Mada Mairam is shown. The novelty of the study lies in the fact that the ethnographic and folklore materials introduced into scientific circulation for the first time made it possible to establish the time at which the annual celebration in honor of Мidğæw took place, as well as to determine the functions of this sanctuary. The author comes to the conclusion that the Мidğæw sanctuary was revered as the heavenly patron of the village of Lisri. Near it, the reconciliation of the bloodlines took place, which testifies to its high sacral status. Previously unpublished archival materials testify to the connection of the Мidğæw sanctuary in the village of Lisri with some sanctuaries in other gorges of Ossetia, which may indicate the existence of an independent Мidğæw cult dating back to the Koban era.